Why did the use of force go up? Investigating the unexpected impact of a body-worn camera program on a use of force time series. (September 2022) - Boehme, Hunter M.; Schnell, Cory
Abstract: Purpose: This study uses an interrupted time series research design to investigate the impact of a body-worn camera (BWC) program on a large police department. Methods: We estimated a generalized linear model on a time series of monthly use of force and civilian complaint counts from January 2013 to September 2021 ( N  = 105) and controlled for other confounding influences. Results: We observed a statistically significant increase in use of force incidents after the implementation of the BWC program. In comparison, the time series for civilian complaints experienced a statistically significant decrease over the same period. There was a substantial increase in use of force incidents during the early 2020s even after accounting for the BWC program. This period was defined by major social disruptions and civil unrest such as the protests surrounding George Floyd's death and the COVID-19 pandemic. Conclusions: Despite the large number of previous evaluations of BWC programs these results are categorically distinct. The most plausible explanations for these findings are officers either increased reporting of use of force incidents or felt more confident using force because of this oversight. Future research should explore how major events of the early 2020s impacted police-civilian encounters across disparate communities. Highlights: Use of force incidents increased after the implementation of body-worn cameras Civilian complaints decreased after the implementation of body-worn cameras An additional increase of use of force after George Floyd's death and COVID-19 These findings are outliers compared to previous program evaluations We propose a body-worn camera "confidence hypothesis" to unpack these findings